New species of Abyssocladia and two new cladorhizid genera (Porifera, Cladorhizidae) from New Zealand and Australia - Kelly, Michelle; Vacelet, Jean; Hestetun, Jon; Mills, Sadie (Zootaxa, 2023)
Seamounts on subantarctic New Zealand’s Macquarie Ridge, including parts of Australia’s Exclusive Economic Zone surrounding Macquarie Island, have been demonstrated to be a rich source of new species of carnivorous sponges (Demospongiae Sollas, Poecilosclerida Topsent, Cladorhizidae Dendy). Four new species of Abyssocladia Lévi, 1964, are described from Macquarie Ridge seamounts and at other disparate locations: Abyssocladia lanceola sp. nov. from Seamounts 7, 8, and 9 (Australia EEZ), Seamount 10 (International Waters), and the South Tasman Rise; Abyssocladia rowdeni sp. nov., first collected from diffuse hydrothermal vent sites at Brothers Seamount on the Southern Kermadec Ridge and recorded here from the non-venting seamounts on Chatham Rise to the east of the South Island of New Zealand; Abyssocladia tumulorum sp. nov., found exclusively on the Chatham Rise; and Abyssocladia sonnae sp. nov. from Monowai Seamount on the Tonga-Kermadec Ridge in International Waters, also found, surprisingly, on Macquarie Ridge’s Seamount 8 (Australia EEZ). Patriciacladia gen. nov. has been established for a new species of Cladorhizidae discovered on Macquarie Ridge and Chatham Rise. Patriciacladia enigmatica gen. et sp. nov. is highly unusual in that it possesses palmate isochelae not typically found in Cladorhizidae and has a long branch in phylogenetic analysis of the family, supporting the establishment of a new genus and species for Abyssocladia n. sp. B (QM G339872, was NIWA 41033): 28S rDNA: LN870583, COI: LN870445, Macquarie Ridge) in Hestetun et al. (2016a: table 1; 2017: fig. 15). The discovery of two new species, again from the Macquarie Ridge and other New Zealand locations, expands support for the establishment of a new genus, Australocladia gen. nov., which contains several additional species nested as a monophyletic clade within the large, heterogenous, and paraphyletic Abyssocladia clade in molecular phylogenetic analyses. Australocladia sphaerichela gen. et sp. nov. and Au. alopecura gen. et sp. nov. both possess spherical abyssochelae, funnel-shaped expansions which may contain spermatophores on the body, substrongyles in the attachment base, and a generally southern hemisphere distribution.